Clinical antidiabetic medication used in Alzheimer’s disease: From basic discovery to therapeutics development - Huang, Juan; Huang, Nanqu; Cui, Di; Shi, Jingshan; Qiu, Yu (Frontiers in Aging Neuroscience, 2023)
Alzheimer's disease (AD) is a common neurodegenerative disease. Type 2 diabetes mellitus (T2DM) appears to increase and contributing to the risk of AD. Therefore, there is increasing concern about clinical antidiabetic medication used in AD. Most of them show some potential in basic research, but not in clinical research. So we reviewed the opportunities and challenges faced by some antidiabetic medication used in AD from basic to clinical research. Based on existing research progress, this is still the hope of some patients with special types of AD caused by rising blood glucose or/and insulin resistance.